PENGARUH GAYA HIDUP, SUASANA TOKO DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA GIGGLE BOX CAFE & RESTO SEMARANG - Gladis Pungky Suharto (Universitas Diponegoro, 2017)
The development of more modern area make a change for trend or lifestyle in society. Modern society who came in restaurant or cafe is not only for enjoying the food and drink, but also to enjoying the atmosphere who created by the cafe. This makes business people in culinary business should consider store atmosphere and service quality at his cafe or restaurant. Store atmosphere and service quality created by the restaurant to be one factorin encouraging of purchase decision. This research was conduted as the sales at Giggle Box Cafe & Resto Semarang continued to fluctuate from February 2014 – February 2016, so we have to know how lifestyle, store atmosphere and service quality influences the purchase decision.The purpose of this study is to find out the influences of lifestyle, store atmosphere and servicce quality to the purchasing decision at Giggle Box Cafe & Resto Semarang. The type of research is explanatory research. Interviews with questionnaire were adopted for dara collection in this study. The selected sample of 100 people by using non-probability sampling technique used is incidental sampling.The research results showed that lifestyle, store atmosphere and service quality influenced on purchase decisions, partially or simultaneously. The results obtained by analyxing the primary data with validity test, reliability test, crosstab analysis, correlation coefficient, simple and multiple regression analysis, the coefficient of detrmination, and significance test ( t and F). The results of this study indicate that there is a strong relationship between the variables in the category of lifestyle, store atmosphere and service quality with the purchase decision where the r value of 0.879. These three independent variables proved to have a positive and significant impact on purchasing decisions. Evidenced by the results of test calculations positive regression coefficient of 0.563 for lifestyle, 0.284 to 0.146 for the store atmosphere and quality of service. Pengauh lifestyle variables have the greatest dar other variables. F-count value amounted to 108.974 larger than F-table (3.938). Based on the results of the study, the researchers suggested that management Giggle Box Cafe & Resto need to improve the design of the room, increase the variety of types of music played, increasing the availability of parking areas